Policy Implementation of City Park Utilization in Malang City: Study of Malang Mayor Regulation No. 90 of 2004 Concerning Utilization of City Park - Aditya Eko Putra; Lely Indah Mindarti; Burhanudin Mukhamad Faturahman (Universitas Islam Darul Ulum Lamongan, 2018)
The provision of services to the community is the main obligation for the Governmentthrough the service delivery process, is to act as a catalyst that accelerates the process inaccordance with procedures. Policy as a series of actions / activities proposed by aperson, group or government in a particular environment where there are obstacles(difficulties) and opportunities for implementing the proposed policy in order to achievecertain goals. The research used in this study is descriptive research with a qualitativeapproach. The focus of this research was taken based on the policy implementation modelproposed by the Model George C. Edward III. 4 (four) variables that influence policyimplementation, namely communication, resources, disposition, and bureaucraticstructure. The results of the study show that the implementation of Malang MayorRegulation No. 90 of 2004 concerning Recommendations for City Park Utilization in theHousing and Settlement Areas of Malang City Parks has not been running optimally. Thisis seen from the uneven distribution of information regarding recommendations for theuse of the park to the people of Malang City. In addition, there is still a lack of facilitiesand infrastructure in delivering information regarding permits to use the park. There arestill deficiencies in the variables resulting in the implementation of the policy has notbeen successful. So that improvements are still needed in each system.